First report of Bipolaris cynodontis on Oryza sativa in Morocco - ZEHHAR, GHIZLANE; TOUHAMI, AMINA OUAZZANI; DOUIRA, ALLAL (Phytopathologia Mediterranea, 2008)
Bipolaris cynodontis was isolated for the fi rst time from Oryza sativa leaves in northwestern Morocco. The pathogenicity of three isolates of B. cynodontis was compared by inoculating the isolates on the leaves of three rice varieties. All the isolates developed similar foliar lesions that differed from those caused by other species of Bipolaris pathogenic on rice.